Policies for inclusive education practices in teacher education in the United Kingdom and France - Malet, Régis (European Journal of Education, 2023)
Implementation of any inclusive policy is dependent on longstanding conceptions, beliefs, and public discourses on schooling, learning, and including children in mainstream schooling. The adoption of inclusive education in education policies in France and the United Kingdom requires discursive support to reshape the meaning and content of teachers' work, duties and practices. Although inclusive education is widely debated, analyses of the variations in policy narratives promoting inclusive teaching in Europe are lacking. This article reports on comparative and international analysis of discourses and policies for empowering teachers for continuous professional development and inclusive school practices. The analysis focuses on an exploration of varieties of articulations, resources, and conceptual dynamics in the UK and France. These elements are discussed within the broader scheme of the teaching profession, with reference to the inclusive education paradigm.